OPTIMIZING ADOLESCENTS AS PROSPECTIVE BRIDES AND GROOMS IN BUILDING A HEALTHY GENERATION WITHOUT STUNTING IN JOMBANG REGENCY: OPTIMIZING ADOLESCENTS AS PROSPECTIVE BRIDES AND GROOMS IN BUILDING A HEALTHY GENERATION WITHOUT STUNTING IN JOMBANG REGENCY - Asmoro, S.Kep.Ns., M.Kep (Dr. Candidate), Candra Panji; Hariyono; Andri Setiya Wahyudi; Suprini Bangngu, Wahyuni; Binnoni Sanam, Hagai (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Stunting is a major nutritional problem in Indonesia that remains unresolved. Jombang is a regency in East Java Province. The prevalence of stunting in Jombang Regency remains high, based on 2024 e-PPBGM data. Stunting itself is a nutritional problem that can be reduced. Jombang Regency has a demographic bonus, namely a high number of adolescents. Adolescents are prospective brides and grooms who can play a role in producing healthy, stunting-free future generations. The problem is that adolescents' knowledge of their role in stunting prevention is lacking. Allowing this situation to persist could impede the government's long-term goal of reducing stunting rates. The solution to address this problem is providing education to increase adolescents' knowledge about stunting and their role in stunting prevention. The educational material was generally about stunting, but there was additional material on the topic of stunting that was in accordance with the characteristics of stunting in adolescents in Jombang Regency. The implementation of activities began with seminars and training on reporting suspected stunting among adolescents. This activity can enhance adolescents' understanding of stunting and the procedures for reporting suspected cases in their local area.